Enhancing Environmental Preservation through Biomethanation of Solid Waste from the Sisal Industries of South Amboasary - Marie, Tolojanahary Jean; Tsirombahy, Soja Lahara; Boni, Randrianjaka; Razafimahatratra, Razafimahatratra; Antoine, Herisoa; Christian, Manjovelo Sambany; Daniel, Razafindrazanakolona; Ngbolua, Koto-te-Nyiwa; Baholy, Robijaona Rahelivololoniaina; Ruphin, Fatiany Pierre (Budapest International Research and Critics University, 2024)
The primary objective of this study is to explore sustainable alternatives to address the accumulation of waste resulting from the sisal exploitation in South Amboasary. Laboratory tests involving 8,000 g of defibration residues mixed with 1,600 g of inoculum over 69 days produced 355 liters of biogas, equating to 335 L/kg of dry matter with a methane content of 58% and a lower calorific value of 20,807 kJ/Nm³. These results suggest that biomethanation can valorize the 212,630 tons of sisal waste available annually, potentially replacing the 2,030 m³ of diesel consumed each year and meeting the domestic fuel needs of 16,575 households with eight members each. Additionally, a production of 137,800 tons of compost is projected to prevent the emission of approximately 7,000 tons of CO₂-equivalent toxic gases into the atmosphere. The technical feasibility studies for infrastructure implementation and project organization address several issues: local treatment of organic waste, creation of local jobs, energy independence, agricultural sustainability, and economic development.